Surface Quality after Grinding VACO 180 Tool Steel using Different Cutting Conditions - Baksa, Tomas; Farsky, Jindrich; Hronek, Ondrej; Zetek, Miroslav (Manufacturing Technology Journal, 2019)
This paper is focused on research in the field of grinding VACO 180 tool steel. Different grinding conditions in terms of several cutting speeds and depths of cut were used for grinding tool steel with CBN grinding wheels. Two CBN grinding wheels with different grain sizes were used for several tests with the same grinding strategy. The influence of the cutting speed and depth of cut on the surface roughness was observed. The different behaviour of both grinding wheels was found during grinding in terms of achieved surface roughness. Higher grain size of the grinding wheel led to higher surface roughness, which increased with cutting speed. However, grinding with deeper cuts showed the opposite effect, and the surface roughness was better at higher cutting speeds. Lower grain size gave a more stable grinding process in terms of achieved surface roughness and lower influence of the cutting speed. However, greater wheel wear occurred during grinding with greater depth of cut. The grinding wheel was dressed before each test to ensure the same grinding ability. The results of this work will be used for a better understanding of the process of grinding tool steel.
Keywords: Grinding; Cutting conditions; Roughness; Tool steel